Oxidative Entry into the Illicium Sesquiterpenes: Enantiospecific Synthesis of (+)-Pseudoanisatin - Hung, Kevin; Condakes, Matthew L; Morikawa, Takahiro; Maimone, Thomas J (Journal of the American Chemical Society, 2016)
Illicium sesquiterpenes have been the subject of numerous synthetic efforts due to their ornate and highly oxidized structures as well as significant biological activities. Herein we report the first chemical synthesis of (+)-pseudoanisatin from the abundant feedstock chemical cedrol (∼$50 USD/kg) in 12 steps using extensive site-selective C(sp3)–H bond functionalization. Significantly, this work represents a novel oxidative strategic template for future approaches to these natural products and their analogs.